Src Family Kinase Inhibitors Block Translation of Alphavirus Subgenomic mRNAs - Broeckel, Rebecca (Antimicrob Agents Chemother, 2019)
Alphaviruses are arthropod-transmitted RNA viruses that can cause arthralgia, myalgia, and encephalitis in humans. Since the role of cellular kinases in alphavirus replication is unknown, we profiled kinetic changes in host kinase abundance and phosphorylation following chikungunya virus (CHIKV) infection of fibroblasts. Based upon the results of this study, we treated CHIKV-infected cells with kinase inhibitors targeting the Src family kinase (SFK)–phosphatidylinositol 3-kinase (PI3K)–AKT–mTORC signaling pathways. Treatment of cells with SFK inhibitors blocked the replication of CHIKV as well as multiple other alphaviruses, including Mayaro virus, O’nyong-nyong virus, Ross River virus, and Venezuelan equine encephalitis virus. Dissecting the effect of SFK inhibition on alphavirus replication, we found that viral structural protein levels were significantly reduced, but synthesis of viral genomic and subgenomic RNAs was unaffected. By measuring the association of viral RNA with polyribosomes, we found that the SFK inhibitor dasatinib blocks alphavirus subgenomic RNA translation. Our results demonstrate a role for SFK signaling in alphavirus subgenomic RNA translation and replication. Targeting host factors involved in alphavirus replication represents an innovative, perhaps paradigm-shifting, strategy for exploring the replication of CHIKV and other alphaviruses while promoting antiviral therapeutic development.